EVALUATION THE IMPACT OF HEALTH INSURANCE POLICIES ON THE AMOUNT OF INFORMAL SECTOR PAYMENTS FOR HEMODIALYSIS SERVICES - Andreastra, Agustinus Putu; Nayoan, Christina Rony; Muntasir, Muntasir; Littik, Serlie K. A.; Weraman, Pius (Universitas Padjadjaran, 2024)
Background : Chronic kidney disease is a condition of kidney damage which is characterized by a progressive decline in kidney function over several months or years so that the kidneys cannot maintain metabolic, fluid/electrolyte balance which results in uremia, and if not treated properly, This disease can cause death, therefore Chronic kidney disease patients need hemodialysis therapy. Chronic kidney disease patients increase every year, data patients at Ruteng Hospital is 35 patients and 8 people are participants in the informal sector of the National Health Insurance. The national health insurance policy is regulated in Presidential Decree No. 64 of 2020. This regulation is intended to re-regulate several aspects of program implementation, starting from increasing the amount of contributions, types of participation, the ecosystem of the national health insurance program, governance of subsidies by the Government for participants. Objective: Analyze and evaluate completely, in detail and systematically in connection with the implementation of the national health insurance policy on the amount of informal sector payments for hemodialysis services at Ruteng Hospital. Method: The research design used is a qualitative approach using descriptive analytical methods by collecting data from participants through in-depth interviews. This research was conducted at Ruteng Hospital. The population was 35 hemodialysis patients. The sampling technique was purposive sampling, taken from samples that met the inclusion criteria: the main participants were 7 patients and the supporting participants were 6 employees. Data collection techniques use primary and secondary data through interviews and documentation, data validity uses triangulation and data analysis uses thematic analysis. Results: dialysis patients only understand the usefulness of the national health insurance program to facilitate their health services in terms of costs and facilities without exploring all the elements contained in the program, the quality of service is very satisfying for dialysis patients both in terms of completeness of facilities and infrastructure as well as other supporting facilities, the safety of their care is guaranteed both in terms of ease of accessing program services and quality and other resources, the impact of the increase in rates shows that Hemodyalisis patients feel objections, resulting in negative impacts, moving treatment classes to lower classes and there are payment in arrears but there are no non-active participants and the positive impact is that there is an increase in the provision of higher quality health services and Health Social Security Agency can experience a surplus, there is an increase in the quality of health and productivity of life for Hemodyalisis patients in maintaining resilience and sustainability as well as social welfare. Conclusion: Health Social Security Agency always carries out monitoring and evaluation in connection with the determination of policies regarding determining the amount of national health insurance contributions based on the financial situation and conditions of the community and taking into account the ability of the State treasury to allocate a budget to subsidize various program operational costs while maintaining and improving system governance National health insurance, for Ruteng Hospital to always improve the quality of services in order to achieve patient satisfaction, for Hemodyalisis patients to be involved in providing contributions in the form of suggestions and criticism to the Government in formulating policies and to be involved in evaluating the national health insurance program.